Moment-based analysis of pinning synchronization in complex networks with sign inner-coupling configurations - Yu, Yanying; Xiang, Linying; Liu, Bo; Xia, Chengyi (Frontiers in Physics, 2023)
In this paper, pinning synchronization of complex networks with sign inner-coupling configurations is investigated from a moment-based analysis approach. First, two representative nonlinear systems with varying dynamics parameters are presented to illustrate the bifurcation of the synchronized regions. The influence of sign inner-coupling configurations on network synchronizability is then studied in detail. It is found that adding negative parameters in the inner-coupling matrix can significantly enhance the network synchronizability. Furthermore, the eigenvalue distribution of the coupling and control matrix in the pinned network is estimated using the spectral moment analysis. Finally, numerical simulations are given for illustration.